Determinan Likuiditas Pasar di Bursa Efek Indonesia - Sundari Oktaviana; Adler Haymans Manurung; Wirawan Widjanarko; Muhammad Richo Rianto; Jhonni Sinaga (Master Manajemen, 2024)
One of the barometers used by investors to invest in the capital market is by looking at the high level of liquidity. The higher the liquidity of a market, the easier it will be for investors to sell and buy assets according to their portfolio needs and market developments. By evaluating and analyzing the determinants of market liquidity in Indonesia, it can be concluded which factors can affect market liquidity positively or negatively. This study aims to analyze whether variables such as return volatility, market return, and foreign ownership have an influence on market liquidity recorded in the Indonesia Stock Exchange (IDX) from January 2012 to December 2023. This research uses secondary data as a data source and a quantitative approach method. The population used in this study is companies listed in the Business-27 index. The sampling technique used in this study is a purposive sampling method. The results of this study show that return volatility has a positive and significant effect on market liquidity, market return has a negative and insignificant effect on market liquidity, and foreign ownership has a negative and significant effect on market liquidity.